The correlation between health beliefs and family support on the elderly’s participation in the Elderly Health Service (Posyandu Lansia) - Wawomeo, Aris; Kurnia, Theresia Avila; Sekunda, Maria Salestina; Fredimento, Aurelius (YCAB Publisher & IAKMI SULTRA, 2022)
Background: Longer life expectancy in Indonesia is a sign for the government to intensively improve various programs for the elderly for better welfare and quality of life. Elderly Health Service (or Posyandu Lansia) that is well-conducted will provide convenience for the elderly in accessing basic health services to maintain and optimize their quality of life. Objective: This research aimed to analyze the relationship between beliefs on health and family support toward the participation of the elderly in Posyandu Lansia. Methods: This correlational research was performed using a cross-sectional approach on 30 elderly selected purposively. The Health Belief Model (HBM) was used as a framework in this study. Data were collected using validated questionnaires and analyzed using univariate statistics, Chi-square, and logistic regression. Results: The results indicated the presence of a correlation between health beliefs, especially perceived vulnerability (p = 0.048) and perceived benefits (p = 0.030), and family support in the elderly’s participation in Posyandu Lansia. Conclusion: It is essential for the public health centers to monitor and approach the families of elderlies who rarely attend Posyandu Lansia to improve their health and quality of life.